A qualitative study of cancer survivors' responses to information on the long‐term and late effects of pelvic radiotherapy 1–11 years post treatment. (22nd July 2015) - Boulton, M.; Adams, E.; Horne, A.; Durrant, L.; Rose, P.; Watson, E.
<x xml:space="preserve">Abstract</x> As more patients survive cancer for longer term, the long‐term and late effects of treatments become increasingly important issues for cancer survivors and providing information to enable survivors to recognise and manage them becomes an increasingly pressing challenge for health care professionals. The aim of this study was to explore the experiences of cancer survivors regarding information given on potential long‐term and late effects of pelvic radiotherapy. Semi‐structured interviews were conducted with 28 cancer survivors who had had radiotherapy to the pelvic area for a range of cancers 1–11 years previously. Participants were recruited using maximum variation sampling from a larger questionnaire survey of patients treated at one hospital. Interviews were recorded, transcribed and analysed using Framework. Participants recognised the value of information to reassure and to inform action but also its potentially undesirable effects to frighten or raise anxieties about future problems and its inherent limitations in meeting their wider needs. They identified the timing, amount of information and context in which it was given as of particular importance. Information based on personal experience was also valued. These findings highlight the importance of appropriate, individualised information during treatment, at hospital discharge and subsequently in primary care.